Unveiling the Properties of Thai Stingless Bee Propolis via Diminishing Cell Wall-Associated Cryptococcal Melanin and Enhancing the Fungicidal Activity of Macrophages - Ketsaya Mamoon; Patcharin Thammasit; Anupon Iadnut; Kuntida Kitidee; Usanee Anukool; Yingmanee Tragoolpua; Khajornsak Tragoolpua (MDPI AG, 2020)
Cryptococcus neoformans, a life-threatening human yeast pathogen, has the ability to produce melanin, which is one of the common virulence factors contributing to cryptococcal pathogenesis. This virulence factor is closely associated with the cryptococcal cell wall, specifically chitin and chitosan polysaccharides, a complex structure that is essential for maintaining cellular structure and integrity. In this study, we aim to investigate the effects of two stingless bee (SLB) propolis from Tetragonula laeviceps and Tetrigona melanoleuca against cell wall-associated melanin in C. neoformans, and its immune response in RAW 264.7 macrophage. The ethanolic extract of SLB propolis (EEP) has strongly exhibited anti-cryptococcal activity. Moreover, EEP from both sources reduced chitin/chitosan and melanin production against C. neoformans in a dose-dependent manner. Likewise, the mRNA expression level of CDA1, IPC1-PKC1 and LAC1 genes involved in the cryptococcal melanization pathway was significantly decreased at 2 mg/mL in EEP treatment. Additionally, pretreatment with EEP prior to yeast infection dramatically reduced intracellular replication of C. neoformans in RAW 264.7 macrophages in a dose-dependent manner. This study might be a new insight to use a natural powerful source, not only acting to target cell wall-associated molecules, but also being capable to explore a novel strategy by which dysregulation of these molecules leads to promote immunomodulatory activity.